Implementasi Sistem Kontrol Pengaturan Penyiraman Air Dan Pemberian Pupuk Otomatis Untuk Tanaman Kangkung Air - Tijaniyah Tijaniyah; Alaika Nurir Robi; Ahmad Sarikul Khoir (Jurnal JEETech, 2022)
Water spinach (Ipomoea aquatic) is a vegetable plant that is needed by the community to meet their daily needs. In addition to the cheap price, kale is also good for health, especially preventing diabetes, overcoming anemia, preventing dehydration as well as increasing the immune system. Therefore, water spinach requires automatic watering and fertilizer application to help hydroponic kale farmers in good and efficient care. It can use a control system tool that can run water irrigation and automatic liquid fertilizer application. The tools used are microcontroller, flow sensor, Wemos D1, Soil Moisture Sensor, Real Time Clock, Relay, LCD 1602, and Servo Motor. In addition, using telegram bots as a final notification to hydroponic kale farmers that watering and fertilizer application has been completed, this is synchronized with the control system tool which provides input on the performance of the tool being late. So with the problems above, the author gives the title "Implementation of Control System for Water Sprinkling and Automatic Fertilizer Provision for Hydroponic Water spinach (Ipomoea Aquatic) Plants").